A Primer on Sovereign Debt Buybacks and Swaps - Polan, Magdalena (IMF Working Papers; Working Paper ;, 2007)
This paper sets forth some basic principles that could help debt managers in emerging market and other countries to plan and implement sovereign debt buyback and swap operations. It discusses the macroeconomic context in which buybacks and swaps are undertaken, the objectives of buybacks and swaps, the analytical framework for deciding whether to undertake a particular buyback or swap operation and for selecting among alternative operations, and some key issues in the determination of the strategy for executing buybacks and swaps. The focus is on developing the analytical framework for evaluating sovereign debt buyback and swap operations, since very little work has been done in this area. In this regard, the paper presents a step-wise decision-making procedure, in which discounted cash flow analysis and the use of strategic benchmarks for the debt play central roles.